An improved and efficient strategy for the total synthesis of a colistin-like peptide. Issue 17 (27th April 2016) - Ramesh, Suhas; Govender, Thavendran; Kruger, Hendrik G.; Albericio, Fernando; de la Torre, Beatriz G.
Graphical abstract: Highlights: Orthogonal protecting groups facilitate the synthetic strategy. Cyclization in a volatile solvent is key for straightforward work-up. The strategy proposed herein can be adapted to other cyclic peptides. Abstract: Polymyxins have re-emerged as the last-line therapy for treatment against extremely multi-drug resistant Gram-negative bacteria, which pose a global threat to public health. Colistin is a polymyxin antibiotic which is effective against most Gram-negative bacteria. Herein, we report a facile and convenient synthesis of a colistin analogue. All the Dabs were protected as Boc groups except for Dab4 which was Alloc protected and used for cyclization with Thr10. The choice of Boc over other protecting groups was to enhance the solubility of the peptide. Cyclization in a volatile solvent such as DCM under very mild conditions and precipitation of the peptide using water are additional advantages of this protocol which can potentially be used for bulk production. The colistin analogue revealed good antibacterial activity in comparison to the natural version.